2021
DOI: 10.1021/acs.jpcc.1c06741
|View full text |Cite
|
Sign up to set email alerts
|

Nature of Oxygen Adsorption on Defective Carbonaceous Materials

Abstract: Plane-wave density functional theory has been used to study oxygen adsorption on graphene, graphite, and (12,0) zigzag single-walled carbon nanotubes with and without Stone–Wales (SW) and single-vacancy (SV) defects to understand the role of defects on carbonaceous material reactivity. Atomic oxygen adsorption leads to the formation of an epoxide on defect-free graphene and graphite and an ether on the exterior wall of carbon nanotubes and SW-defected materials. O2 chemisorption is endothermic on defect-free g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 66 publications
1
4
0
Order By: Relevance
“…The adsorption energy of oxygen on the perfect graphene surface (Situation 1) (−0.22 eV) is significantly higher than that on G sw defect (Situation 2) (−3.45 eV), indicating that the defect centers are more preferential to absorb oxygen and to be oxidized. This is consistent with the previous reports that graphene oxidation generally started from the defects since the carbon atoms at the defective centers can donate more electrons to oxygen . In contrast, the adsorption energy of oxygen above the h -BN-encapsulated G sw defect (Situation 3) increases significantly, along with the reduced adsorption life, which implies that the encapsulation of h -BN can hinder oxygen adsorption and mitigate graphene oxidation.…”
Section: Results and Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The adsorption energy of oxygen on the perfect graphene surface (Situation 1) (−0.22 eV) is significantly higher than that on G sw defect (Situation 2) (−3.45 eV), indicating that the defect centers are more preferential to absorb oxygen and to be oxidized. This is consistent with the previous reports that graphene oxidation generally started from the defects since the carbon atoms at the defective centers can donate more electrons to oxygen . In contrast, the adsorption energy of oxygen above the h -BN-encapsulated G sw defect (Situation 3) increases significantly, along with the reduced adsorption life, which implies that the encapsulation of h -BN can hinder oxygen adsorption and mitigate graphene oxidation.…”
Section: Results and Discussionsupporting
confidence: 91%
“…This is consistent with the previous reports that graphene oxidation generally started from the defects since the carbon atoms at the defective centers can donate more electrons to oxygen. 53 In contrast, the adsorption energy of oxygen above the h-BN-encapsulated G sw defect (Situation 3) increases significantly, along with the reduced adsorption life, which implies that the encapsulation of h-BN can hinder oxygen adsorption and mitigate graphene oxidation.…”
Section: Theoretical Investigations Of the Mechanisms For The Enhance...mentioning
confidence: 99%
“…The redox reaction mechanism is commonly used to explain the sensitivity mechanism of metal oxide SnO 2 . SnO 2 materials are N-type semiconductor materials with a broad bandgap (3.6 eV), and, under normal conditions, the internal O 1s are usually composed of two types of oxygen; one is lattice oxygen (O lat ), and the other is adsorbed oxygen (O ads ) on the surface [ 37 , 38 ]. In the air, ion-adsorbed oxygen generates spatially induced charges on the semiconductor surface and creates surface potential barriers that bend the energy band upward, resulting in a decrease in the surface mobility of the SnO 2 material due to the decrease in the electron concentration after the adsorption of oxygen.…”
Section: Resultsmentioning
confidence: 99%
“…[ 77 ] Mechanisms of O 2 chemisorption and the evolution of functional groups on graphene are part of an actively developing area of research. [ 78 ] In independent theoretical calculation it was consistently found that vacancy defects in graphite (0001) surfaces, [ 79 ] graphene sheets, [ 80,81 ] and CNTs [ 81 ] lower the energy barrier for dissociative chemisorption drastically, for example, from 270 kJ/mol for defect‐free graphene to less than 30 kJ/mol for a single‐vacancy defect. Low‐energy ion bombardment is known to induce defects in graphene sheets.…”
Section: Resultsmentioning
confidence: 99%